Inequality at Work: The Effect of Peer Salaries on Job Satisfaction - Card, David; Mas, Alexandre; Moretti, Enrico; Saez, Emmanuel (American Economic Review, 2012)
We study the effect of disclosing information on peers' salaries on workers' job satisfaction and job search intentions. A randomly chosen subset of University of California employees was informed about a new website listing the pay of University employees. All employees were then surveyed about their job satisfaction and job search intentions. Workers with salaries below the median for their pay unit and occupation report lower pay and job satisfaction and a significant increase in the likelihood of looking for a new job. Above-median earners are unaffected. Differences in pay rank matter more than differences in pay levels. (JEL I23, J28, J31, J64)